As três religiões do livro - João Gouveia Monteiro (Documentos, 2012)
"There will be no peace between nations without peace between religions. There will be no peace between religions without dialogue between religions. There will be no dialogue between religions without global ethical criteria. There will be no survival for our world with peace and justice without a new paradigm of international relations based on global ethical standards." In the light of this declaration, made by the famous theologian Hans Küng in the General Assembly of the United Nations in November 2001 (in the line of the "Declaration of a World Ethics" approved in 1993 by a Parliament of World Religions which brought together in Chicago over 200 representatives of all the religions of the world), Coimbra University Press invited a group of specialists to meet in November 2010 to discuss the premises and current conditions for inter-religious dialogue. The initiative, which brought together representatives and scholars of the prophetic religions (the three great Abrahamic religions or 'religions of the book': Judaism, Christianity and Islam) and the mystical religions, aroused a great deal of interest, which proves the urgency of this discussion in the present world. This volume serves as the memory of that event and also aims to be a contribution and a motivation for other similar initiatives.